2013
DOI: 10.3796/ksft.2013.49.1.029
|View full text |Cite
|
Sign up to set email alerts
|

Study on the marine casualties in Korea

Abstract: Fishing vessels have been causing more than 70% of marine casualty in Korea. As a view of the occurring number of marine casualty, it is obvious for fishing vessel to account for the absolute high portion of that in comparison with the non-fishing vessels. That is a natural outcome because fishing vessels have occupied more than 90% of all registered Korean vessels. If we consider it not occurring number, but occurring ratio, we could find out that fishing vessels accounted for 5 times lower than non-fishing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…With their approach, strategic action plans were developed for minimizing shipping casualties. Kang et al studied the marine casualties, especially the collision and the machine damage, in Korea [7]. They suggested that, it is necessary for the seafarer to take more education and training, especially for the crews of fishing vessels.…”
Section: Introductionmentioning
confidence: 99%
“…With their approach, strategic action plans were developed for minimizing shipping casualties. Kang et al studied the marine casualties, especially the collision and the machine damage, in Korea [7]. They suggested that, it is necessary for the seafarer to take more education and training, especially for the crews of fishing vessels.…”
Section: Introductionmentioning
confidence: 99%
“…이제까지 우리나라의 해양사고에 대해 적지 않은 연 구들이 수행되어 왔으나 (Kang and Koh, 1995;Park and Kang, 1995;Kang et al, 2007;Chang, 2009) (Kang et al,. 2013).…”
unclassified